Circulation of single serotype of Dengue Virus (DENV-3) in New Delhi, India during 2016: A change in the epidemiological trend. Issue 1 (January 2019) - Parveen, Nazish; Islam, Arshi; Tazeen, Ayesha; Hisamuddin, Malik; Abdullah, Mohd; Naqvi, Irshad H.; Faizan, Md I.; Gulyani, Divya; Ahmed, Anwar; Parveen, Shama
Abstract: Background: Dengue is a rapidly emerging arthropod borne viral infection affecting tropical and sub-tropical regions of the world. Dengue is an acute febrile illness but sometimes causes more fatal complications like dengue haemorrhagic fever (DHF) and dengue shock syndrome (DSS). Delhi, the capital of India has become hyper endemic for dengue virus because all the four serotypes are circulating here. Methods: The present study describes the identification of dengue virus from clinical samples collected from the suspected dengue patients from New Delhi, India during 2016. The CprM region of Dengue virus genome was analyzed for phylogenetic, selection pressure and Shannon entropy analyses. Results: The present study reports circulation of a single serotype (DENV-3) in New Delhi, during 2016. The phylogenetic analysis revealed that Indian subcontinent (genotype III) of DENV-3 was circulating in Delhi during this period. Neutral selection pressure in the analyzed region revealed relatively conserved nature of this part of the Dengue virus genome. Amino acid at 31 was positively selected and had high entropy value suggesting probability of variation at this position. Conclusions: The changing trend in circulation of dengue virus serotypes necessitates the continuous epidemiological surveillance for the dengue outbreaks in this region.